DAMPAK PROGRAM MUSIM TANAM 2 KALI (MT2) TERHADAP MASYARAKAT - M. Nur Ramadhan; Wijayanti, Ayu (JURNAL ILMIAH IDEA, 2023)
This study aims to examine the impact of the MT2 program on the people of Talang Leak I and II Villages. The village community is one sector that is of concern in national development. This program is aimed at increasing welfare and strengthening the socio-economic structure at the village level. This research method uses a qualitative approach by conducting case studies in two villages that are included in the program. Data was collected through participatory observation, in-depth interviews, and document analysis related to government programs. The results of this study indicate that the MT2 program has a significant impact on the community.